AL-FARABI POLITICAL THOUGHT - A . M . Dr. Nizar Amer Hussein (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Praise be to Allah, Lord of the Worlds, and peace and blessings be upon, Prophet Muhammad, the last of the prophets and messengers, onhim and his family and companions. Now to our topic, writing about the thought of scientists, philosophers and innovators is not an easytask for many researchers. Nevertheless, it is a worthy effort because the deep knowledge of these elites’ ideas gives the readers and researcher a wealth of thoughts. Such wealth can/will enlighten the reader’s mind. The way of presentation of these notions will make the mere observations well-known approaches. The figure that this research will deal with is Al-Farabi, whom is deemed one of the most famous Muslim philosophers in the world. His thought influenced many Muslims and non-Muslims who came after him. His books were translated into many international languages. This research may not be the first one about Al-Farab’spolitical thought and philosophy butit is an attempt to review some of hisphilosophical aspects associated with the policy as well asto be familiar with the historical scene at that time. It also deals with two important philosophical booksof his, namely, Araa’aahelalmadinaalfadihlah(Opinions of the People of the utopia) and aljami’a ben alhakimean (Combining the Opinions of the Wise Men). He wrote many books in poetry and rhetoric, knowledge and logic. His biography, preceding his book review, presents details about his personal and scientific. The research includes an introduction, two sections, and a conclusion.The most important sources of diverse scientific references, used in the scientific materials, are listed. God is the Arbiter of Success.